2019
DOI: 10.1186/s13018-019-1128-7
|View full text |Cite
|
Sign up to set email alerts
|

Allograft or autograft in skeletally immature anterior cruciate ligament reconstruction: a prospective evaluation using both partial and complete transphyseal techniques

Abstract: ObjectiveWe compared autografts and allograft using partial and complete transphyseal anterior cruciate ligament (ACL) reconstruction techniques among skeletally immature individuals.MethodsMale and females younger than 18 and 16 years old, respectively, diagnosed with ACL tear from April 2006 to March 2012 entered the study. One group had four-strand hamstring autograft, and the other had tibialis posterior allograft reconstruction. Those who had allografts either had hyper-laxity or recurvatum.ResultsAchieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 39 publications
(53 reference statements)
4
14
0
Order By: Relevance
“…The mean 2-year IKDC Subjective Score was 85 points in the ACLR group in this trial, which is consistent with the 2-year ACLR scores reported by the MOON group (82 points) 8 and others (86 points). 49 The BEAR group had mean scores at 2 years similar to those in the ACLR group and similar to that reported for an age-matched control cohort (88 points). 3 Given that the lower bound of the confidence interval for the difference was 21.5, the pre-specified noninferiority lower bound (211.5) for the IKDC Subjective Score could have been set much tighter and still been satisfied.…”
Section: Discussionsupporting
confidence: 79%
“…The mean 2-year IKDC Subjective Score was 85 points in the ACLR group in this trial, which is consistent with the 2-year ACLR scores reported by the MOON group (82 points) 8 and others (86 points). 49 The BEAR group had mean scores at 2 years similar to those in the ACLR group and similar to that reported for an age-matched control cohort (88 points). 3 Given that the lower bound of the confidence interval for the difference was 21.5, the pre-specified noninferiority lower bound (211.5) for the IKDC Subjective Score could have been set much tighter and still been satisfied.…”
Section: Discussionsupporting
confidence: 79%
“…Individual study characteristics are summarized in Tables I and II. The average age of participants in individual studies ranged from 14 years 27 to 19 years 38 , and the average duration of follow-up ranged from 24 months 26 to 240 months 34 . The average age of the pediatric/adolescent cohort could not be determined in 3 studies 29 , 34 , 36 .…”
Section: Resultsmentioning
confidence: 99%
“…The sex of participants in individual studies ranged from 25% female 38 to 100% female 31 . One study described allograft ACLR only 30 , 7 studies described autograft ACLR only 27 , 29 , 32 - 34 , 36 , 37 , and 6 studies described both ACL allograft and autograft reconstruction within the same cohort 21 , 26 , 28 , 31 , 35 , 38 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations